Psychological disorders resulting from traumatic experiences and their relationship to depression in a sample of displaced children in some shelters in the southern governorates during the war on Gaza in 2024 (The International Journal of Educational Sciences and Arts, 2024)
The current study aimed to know the correlation level between psychological disorders resulting from traumatic experiences and symptoms of depression for a sample of displaced children in some collective shelters in the southern governorates during the war on Gaza in 2024. The researcher used the irregular random sample in the study, as the study sample consisted of (200) children between (8-10) years and (11-12) years of both genders. The researcher used the descriptive analytical approach in the study, relying on measurement tools to implement the study, which are: the scale of disorders resulting from traumatic experiences - Davison scale - translated by Thabet, Abdul Aziz 2005 - PTSD Scale according to DSM—IV - and Beck Depression Inventory - Beck).Study Findings:-   The traumatic experiences of displaced children in shelters in the southern governorates reached 71.9%, which is significantly high. It was also found that “avoiding situations and things that trigger/remind of the traumatic event” was the largest psychological disorder resulting from traumatic experiences among displaced children in shelters with a relative weight of 76.5%, where 76% of the study sample has ‘always’ or ‘often’ suffered from that experience at 41% and 35% respectively.-   The results showed that the symptoms of depression among displaced children in shelters in the southern governorates were 63%, which indicates that the level of psychological disorders resulting from traumatic experiences among displaced children was high. ‘Feelings of guilt (remorse)’ was the largest source of depression with a relative weight of 69.7%, followed by loss of enjoyment with a relative weight of 68.3%, followed by changes in appetite with a relative weight of 68.3%, followed by fatigue or stress with a relative weight of 67.3%, and followed by changes in sleep patterns with a relative weight of 66.7%.-   The results showed that there is a direct correlation between the level of psychological disorders resulting from traumatic experiences and the level of depression among displaced children in shelters located in the southern governorates.-   The results showed that the overall score of psychological disorders resulting from traumatic experiences among displaced children in shelters had a significance level below 0.05, which is the accepted significance level in the study. It was also found that the calculated t-value was greater than the tabulated value, indicating statistically significant differences at the 0.05 level in the average level of psychological disorders. These differences are attributed to gender, with females showing a higher level of psychological disorders compared to males.-   The results showed that the significance level for the overall depression score among displaced children in shelters was higher than 0.05, which is the significance level accepted by the study. It was also found that the calculated t-value was lower than the tabulated value, indicating no statistically significant differences at the 0.05 level in the average depression levels among displaced children in shelters in the southern governorates attributed to gender.-   The results showed that the significance level for the overall scores of psychological disorders resulting from traumatic experiences and depression among displaced children in shelters was higher than 0.05, which is the significance level accepted by the study. It was also found that the calculated t-value was lower than the tabulated value, indicating no statistically significant differences at the 0.05 level in the average levels of psychological disorders resulting from traumatic experiences and depression among displaced children in shelters in the southern governorates attributed to age.-   The results showed that the significance level for the overall scores of psychological disorders resulting from traumatic experiences and depression among displaced children in shelters in the southern governorates was lower than 0.05, which is the significance level accepted by the study. It was also found that the calculated t-value was greater than the tabulated value, indicating statistically significant differences at the 0.05 level in the average levels of psychological disorders resulting from traumatic experiences and depression among displaced children in shelters in the southern governorates attributed to the type of shelter, in favor of shared shelters.-   The results showed that the significance level for the overall score of psychological disorders resulting from traumatic experiences among displaced children in shelters in the Southern governorates was higher than 0.05, which is the significance level accepted by the study. It was also found that the calculated t-value was lower than the tabulated value, indicating no statistically significant differences at the 0.05 level in the average levels of psychological disorders resulting from traumatic experiences among displaced children in shelters in the southern governorates attributed to receiving psychological services.-   The results showed that the significance level for the overall score of depression among displaced children in shelters in the Southern governorates was lower than 0.05, which is the significance level accepted by the study. It was also found that the calculated t-value was greater than the tabulated value, indicating statistically significant differences at the 0.05 level in the average depression levels among displaced children in shelters in the southern governorates attributed to receiving psychological services, for the favor of children who did not receive psychological services.
Keywords: Disorders Resulting from Traumatic Experiences; Psychological Disorders; Displaced Children; Shelters; Southern Governorates; War on Gaza